THE IMPORTANCE OF KNOWLEDGE IN THE CONTEXT OF CHANGES IN LABOR MARKET (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article made the problem of knowledge as determinants of changes in the labor market. It was assumed that as the main causal agent of socio-economic impact on all dzidziny life, and the process of gaining influence on the efficiency of the labor market and changes in the demand for certain professions and skills reported by small and medium-sized enterprises.
Keywords: labor market, knowledge, human capital, SMEs, qualifications